Comparison of Chest Ultrasound and Standard X-Ray Imaging in COVID-19 Patients - Shumilov, Evgenii; Hosseini, Ali Seif Amir; Petzold, Golo; Treiber, Hannes; Lotz, Joachim; Ellenrieder, Volker; Kunsch, Steffen; Neesse, Albrecht (Ultrasound International Open, 2020)
The COVID-19 pandemic poses new challenges for the medical community due to its large number of patients presenting with varying symptoms. Chest ultrasound (ChUS) may be particularly useful in the early clinical management in suspected COVID-19 patients due to its broad availability and rapid application. We aimed to investigate patterns of ChUS in COVID-19 patients and compare the findings with results from chest X-ray (CRX).24 patients (18 symptomatic, 6 asymptomatic) with confirmed SARS-CoV-2 by polymerase chain reaction underwent bedside ChUS in addition to CRX following admission. Subsequently, the results of ChUS and CRX were compared.94% (n=17/18) of patients with respiratory symptoms demonstrated lung abnormalities on ChUS. ChUS was especially useful to detect interstitial syndrome compared to CXR in COVID-19 patients (17/18 vs. 11/18; p<0.02). Of note, ChUS also detected lung consolidations very effectively (14/18 for ChUS vs. 7/18 cases for CXR; p<0.02). Besides pathological B-lines and subpleural consolidations, pleural line abnormality (89%; n=16/18) was the third most common feature in patients with respiratory manifestations of COVID-19 detected by ChUS.Our findings support the high value of ChUS in the management of COVID-19 patients.
Keywords: coronavirus; SARS-CoV-2; COVID-19; chest ultrasound; X-ray